In Silico Analysis of Glucose Oxidase H516r and H516d Mutations for an Enzymatic Fuel Cell - Puspa Julistia Puspita; Laksmi Ambarsari; Adrian Adiva; Tony Ibnu Sumaryada (Syarif Hidayatullah State Islamic University, 2021)
Glucose oxidase (GOx) is an oxido-reductase enzyme that catalyzes glucose into hydrogen peroxide and glucono delta-lactone (GDL). GOx has the potential to be used in the medical field. Numerous research concerning the usage of GOx to create enzymatic biofuel cells have been done, nevertheless the results obtained have not been optimal. This research aims to increase the Km values of GOx in order to increase its potential as a material for an enzymatic fuel cell. The amino acid histidine in position 516 is a residue in the active site that plays an important part in the process of glucose oxidation. In this research we mutated H516 by in silico twice resulting in the mutants R516 and D516. The mutations resulted in a change of the docking area for both mutants and in the docking affinity for H516D resulting in higher Km values. This shows that the H516 residue plays an important part in the functions of glucose oxidase and mutation into aspartate could improve glucose oxidase based enzymatic fuel cells.